Public performance and the challenge of local collective action strategies: Quebec's experience with an integrated territorial approach - Divay, Gerard (2016)
Evaluating the performance of local environment activation strategies, set forth in many central policies, is an exercise fraught with challenges. Based on an analysis of 10 Integrated Territorial Approach initiatives, which were rolled out in Quebec's fight against poverty, this article proposes a framework to better assess their various effects. These strategies are characterised by a partnership process and a collective focus. Performance occurs at micro-, meso- and macro-levels and is observable not only in the production of deliverables, but also on three other process dimensions, which are characteristic of such strategies: fostering the maintenance of local mobilisation drivers; improving the quality of locally productive elements; and learning strategic coherence. This understanding of collective performance takes public managers out of their comfort zone. Beyond having to develop collaborative skills, as is now well-documented in the literature, it leads them to develop an investor mindset and to become logisticians of the collective, not just efficient service providers. - Reproduced.
Keywords: Local government; Performance appraisal